2020
DOI: 10.46336/ijbesd.v1i3.50
|View full text |Cite
|
Sign up to set email alerts
|

Mispricing and Investor Preference with Six Indicators of Blue-Chip Stocks’ Future Returns

Abstract: This research involves three variables: future returns, mispricing, and investor preference. The issue is that future returns in the markets are difficult to understand, especially for beginner, amateur investors. They are advised to focus on blue-chip stocks due to their safety in the market. The objective of this research is to find a connection from mispricing and investor preference to the future anomalies as indicators of mispricing and ten measurements as indicators of investor preference leading to thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This indicates that the stocks in the KFX index face higher demand or more attention than the stocks outside the index. Iman, Syamruddin, Irwansyah (2020) suggested that the result is not significant for the investor preference and mispricing index for the future returns of blue-chip stocks [3]. However, this study still has some limitations, because this study only includes three U.S. indexes, and it does not rule out that the indexes of other countries and regions will have different changes.…”
Section: Discussionmentioning
confidence: 89%
“…This indicates that the stocks in the KFX index face higher demand or more attention than the stocks outside the index. Iman, Syamruddin, Irwansyah (2020) suggested that the result is not significant for the investor preference and mispricing index for the future returns of blue-chip stocks [3]. However, this study still has some limitations, because this study only includes three U.S. indexes, and it does not rule out that the indexes of other countries and regions will have different changes.…”
Section: Discussionmentioning
confidence: 89%
“…From US listed firms, the firms with top brands have higher stock returns, lower sytematic risk and lower idiosyncratic risk than others (Huang et al, 2021). It might be also similar to Blue Chips in Indonesia (Lubis et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Indonesia Capital Market or IHSG is the lowest risk market among Southeast Asian Countries (Lubis, 2018a). Thus, From many indexes, there are several indexes that are market stability such as development board index, the miscellaneous industry index, the Indonesian FTSE indeks, the LQ-45 index, the 30 stock index , and the sharia index (Lubis, 2018b) From the previous explanation on researches, I could see that during COVID-19 pandemic, almost stock market returns in all of the world found in bear phase except Japanese Market. This fact motivate me to explore the stock market returns which called aset pricing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations